2002
DOI: 10.1097/00007890-200205270-00006
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of anti-Gal B cell receptor transgenic Gal???/??? mice

Abstract: These observations suggest that this model can be used to study the regulation of anti-Gal B cells and can establish a reliable source of functional anti-Gal B cells, which could be used to test the effectiveness of alpha-Gal-specific immunosuppressive reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Characterization of B cell development in the bone marrow of M86V H V L GT 0/0 or M86V H V L GT ϩ/ϩ knock-in mice demonstrated that pro-B cells (B220 ϩ ,CD43 ϩ ) and immature (B220 ϩ ,CD43 Ϫ ) B cells, as defined in (48,49), were present in similar proportions to those observed in normal mice, although the frequency of each of these fractions was reduced when compared with normal controls (Fig. 2A), as observed in other Ig knock-in mice (32,33). The frequency of pre-B cells was similar in M86V H V L GT 0/0 or M86V H V L GT ϩ/ϩ knock-in mice (data not shown).…”
Section: Characterization Of Early Lymphocyte Development In M86v H Vsupporting
confidence: 58%
See 3 more Smart Citations
“…Characterization of B cell development in the bone marrow of M86V H V L GT 0/0 or M86V H V L GT ϩ/ϩ knock-in mice demonstrated that pro-B cells (B220 ϩ ,CD43 ϩ ) and immature (B220 ϩ ,CD43 Ϫ ) B cells, as defined in (48,49), were present in similar proportions to those observed in normal mice, although the frequency of each of these fractions was reduced when compared with normal controls (Fig. 2A), as observed in other Ig knock-in mice (32,33). The frequency of pre-B cells was similar in M86V H V L GT 0/0 or M86V H V L GT ϩ/ϩ knock-in mice (data not shown).…”
Section: Characterization Of Early Lymphocyte Development In M86v H Vsupporting
confidence: 58%
“…However, the frequency of B cells producing ␣Gal specific Abs in these mice is too low to allow for their direct analysis. We and others have previously attempted to overcome this difficulty by generating Ig transgenic mice that express transgenes encoding ␣Gal-specific Abs (32,33). However, these models are limited because the expressed transgenes were not subject to regulation by elements within the endogenous Ig loci, making it difficult to assess physiological relevance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For complement activation, the cells were washed and then incubated with a 1/10 dilution of mouse serum and FITCconjugated anti-mouse C3b (Cappel-Organon Teknika, Durham, NC) or goat anti-sera to human-C5 (Quidel), biotin-conjugated rabbit anti-goat IgG (Vector Laboratories, Burlingame, CA), and streptavidin-FITC (BD PharMingen, San Diego, CA). Anti-Gal mAbs were also assayed for the ability to cause complement-mediated lysis with a hemoglobin release assay as previously reported (10 Received for publication March 1, 2004. Accepted for publication April 16, 2004.…”
Section: Binding and Complement Activation By Anti-gal Mabsmentioning
confidence: 99%